Efficacy, predictability and safety of long-term orthokeratology: An 18-year follow-up study. Issue 1 (February 2022) - Gispets, Joan; Yébana, Pilar; Lupón, Núria; Cardona, Genis; Pérez-Corral, Joan; Pauné, Jaume; Cortilla, Bernat
Highlights: Efficacy and predictability of long-term orthokeratology was good in children and adults. The incidence of microbial keratitis was 6.8 cases per 10, 000 patient-years in adults and no cases were reported in children. Corneal staining remains the most frequent complication of orthokeratology, and it is less frequent and less severe in children. Higher myopia, anterior corneal eccentricity and smaller anterior corneal horizontal radius increased the risk of repeated episodes of corneal staining. Abstract: Purpose: To determine the efficacy, predictability and safety of long-term orthokeratology in children and adults. Methods: Case histories of 300 orthokeratology patients (596 eyes; 34.3% children; 65.7% adults) were reviewed to collect information on demographics, corneal and refractive parameters, visual acuity, residual refraction and adverse effects. Predictability was defined as the percentage of eyes with absolute values of spherical equivalent refraction ≤ 0.5 D of emmetropia, and efficacy as the ratio of post-orthokeratology uncorrected and pre-orthokeratology corrected distance visual acuity. Results: Median duration of treatment was 37 and 28.5 months in children and adults, respectively (p = 0.022). During the first year, 17.2% of children and 33% of adults ceased lens wear (p < 0.001). For children and adults with a successful ortho -k treatment of at least one year of duration, 88.7% and 95.9% of eyes had a predictable refractive outcome, and efficacy was 0.98 and 1.01, respectively. A larger percentage of children (65.7%) were free of complications than of adults (55.4%) (p = 0.015). One event of microbial keratitis occurred in adults (6.8 cases per 10, 000 patient-years) and none in children. Corneal staining was the most frequent complication, with a higher incidence in adults (p = 0.007) and in higher myopia (p < 0.001), higher anterior corneal eccentricity (p = 0.019) and smaller anterior horizontal radius (p = 0.027). Conclusion: Orthokeratology is a safe and predictable long-term procedure in children and adults, with a low incidence of serious adverse effects. Corneal staining episodes are relatively frequent throughout the course of the treatment, thus highlighting the relevance of education of experienced users.